Nonverbal Communication In The Classroom And Its Role In The Teaching And Learning From Educational Process - Zanyar Nathir Ghafar; Hemn Mohammed Ali Hemn Mohammed Ali (Journal Of Social Science (JoSS), 2023)
It has been established that non-verbal communication is a crucial strategy that improves pupils' comprehension. As a consequence, it aids in improved idea acquisition and comprehension. The main goals of this investigation are to look at the value of nonverbal communication in the educational process. Additionally, this essay will cover the purposes and guiding principles of nonverbal interactions in the classroom, as well as some fundamental ways to use nonverbal behaviors to enhance the effectiveness of teaching and the significance of nonverbal contact that learners as well as instructors can fully appreciate. An essential component of instruction is nonverbal communication. The benefit for a teacher is to develop great nonverbal communication skills, including strong sensitivity. The nonverbal signals that are employed in the classroom, such as teachers' facial expressions, postures, gestures, touch, and eye contact, are highly essential in many cultures; thus, teachers and educators should be good listeners in addition to the words that are being uttered. Nonverbal cues in the classroom, however, are seen differently in different cultures throughout the world. For example, some students abhor touching, postures, eye contact, and staring. Instructors should be mindful that, owing to cultural variations, some or all students may not be interested in making eye contact with their presenters due to various learning processes in different cultural behaviors and their viewpoints.